2022
DOI: 10.3389/fphys.2022.858739
|View full text |Cite
|
Sign up to set email alerts
|

Graph Theory Analysis of the Cortical Functional Network During Sleep in Patients With Depression

Abstract: Depression, a common mental illness that seriously affects the psychological health of patients, is also thought to be associated with abnormal brain functional connectivity. This study aimed to explore the differences in the sleep-state functional network topology in depressed patients. A total of 25 healthy participants and 26 depressed patients underwent overnight 16-channel electroencephalography (EEG) examination. The cortical networks were constructed by using functional connectivity metrics of participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The participants reported that the air mattress was softer than the control mattress. Our previous studies indicated that MDD patients showed a consistent enhancement of functional connectivity (Lian et al, 2021;Song et al, 2022;Zhang et al, 2022b), and the female participants exhibited stronger EEG functional connectivity than the male participants (Liao et al, 2019). We are aware that female patients are more likely to suffer from depression (Eid et al, 2019;Gao et al, 2020b) and that patients with depression are more sensitive to the outside environment.…”
Section: Figurementioning
confidence: 97%
“…The participants reported that the air mattress was softer than the control mattress. Our previous studies indicated that MDD patients showed a consistent enhancement of functional connectivity (Lian et al, 2021;Song et al, 2022;Zhang et al, 2022b), and the female participants exhibited stronger EEG functional connectivity than the male participants (Liao et al, 2019). We are aware that female patients are more likely to suffer from depression (Eid et al, 2019;Gao et al, 2020b) and that patients with depression are more sensitive to the outside environment.…”
Section: Figurementioning
confidence: 97%
“…The structural and functional properties of graphs of brain networks can be quantitatively investigated through measures of [ 239 ]: Functional segregation, e.g., clustering coefficients [ 248 , 249 , 250 , 251 , 252 ] and modularity [ 253 ]. Functional integration, based on the concept of path [ 248 , 254 ] and estimating the ease of communication between brain areas.…”
Section: Functional Connectivity Estimation Approachesmentioning
confidence: 99%
“…Functional segregation, e.g., clustering coefficients [ 248 , 249 , 250 , 251 , 252 ] and modularity [ 253 ].…”
Section: Functional Connectivity Estimation Approachesmentioning
confidence: 99%
“…Changes in the organisation of the global network of structural and functional brain connectomes have been illustrated in MDD compared to healthy controls [45]. In general, it is now believed that functional network topology can become a powerful tool for depressive nosological diagnoses [46].…”
Section: Glutamate Receptors and Biomarkersmentioning
confidence: 99%